GLUT1: structure, function, and biomedical significances - Ika Yustisia; Mutmainah Arif (Indonesian Archives and Biomedical Sciences, 2021)
Background; Glucose is the main energy source for cells. To be utilized by cells, glucose enters the intracellular space facilitated by transporters. GLUT1 is one of the glucose transporters and is the most widely expressed by various tissues in the body. Not only that, cancer cells, which are known to have very high glucose requirements compared to healthy cells, have a high expression of GLUT1 as well. Reviews; This paper reviews the structure, function, and biomedical importance of GLUT1 and specifically describes recent developments regarding GLUT1 inhibition as a novel therapeutic approach in both metabolic diseases and cancers. Conclusion; Inhibition of GLUT1 has also been shown to increase cancer cells' sensitivity to chemotherapy agents such as cisplatin and adriamycin. GLUT1 inhibition also increases the sensitivity of cancer cells to radiotherapy.